2020
DOI: 10.1002/rnc.4964
|View full text |Cite
|
Sign up to set email alerts
|

Observer‐based leaderless and leader‐following consensus for multiagent systems: A modified integral‐type event‐triggered design

Abstract: SummaryThis article aims to solve leaderless and leader‐following consensus problems for general linear systems by integral‐type event‐triggered control method. Different from the existing integral‐type event‐triggered controllers for multiagent systems (MASs), a modified distributed integral‐type event‐triggered scheme is designed via defining a measurement error without continuous communication. Then, distributed event‐triggered protocols are proposed for MASs to achieve the leaderless and leader‐following c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The idea of integral‐based event‐triggering condition yielding larger inter‐event intervals was proposed by Mousavi, Ghodrat and Marquez 36 . Later, this idea is applied to MASs in 37 and it has been investigated further in References 38–41. In particular, Zhang, Lunze and Wang 39 showed that the proposed controller system for the consensus problem has a positive MIET and the consensus is achieved asymptotically without a small error.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea of integral‐based event‐triggering condition yielding larger inter‐event intervals was proposed by Mousavi, Ghodrat and Marquez 36 . Later, this idea is applied to MASs in 37 and it has been investigated further in References 38–41. In particular, Zhang, Lunze and Wang 39 showed that the proposed controller system for the consensus problem has a positive MIET and the consensus is achieved asymptotically without a small error.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Zhang, Lunze and Wang 39 showed that the proposed controller system for the consensus problem has a positive MIET and the consensus is achieved asymptotically without a small error. However, there is a gap in the proofs of the consensus for the system in References 38–41 as they applied Barbalat's lemma without proving the uniform boundedness of the derivative of the consensus test function δfalse(tfalse)$$ \delta (t) $$ which is a nontrivial step. To overcome this gap, Ma and Zhao 42 put an extra condition about the boundedness of measurement error functions inside their proposed integral‐based event‐triggering protocol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of integral-based event-triggering condition yielding larger inter-event intervals was proposed by Mousavi, Ghodrat and Marquez [34]. Later, this idea is applied to multiagent systems in [35] and it has been investigated further in [36], [37], [23], [38], [39]. In particular, Zhang, Lunze and Wang [38] showed that the proposed controller system for the consensus problem has a positive MIET and the consensus is achieved asymptotically without a small error.…”
Section: Introductionmentioning
confidence: 99%
“…One essential step in proving the consensus using integral based eventtriggered control is the application of Barbalat's lemma. This step requires obtaining a uniform bound for the derivative V of the a Lyapunov function V used in the proof ( [36], [37], [38], [23], [39]). We give a full detail for obtaining the uniform boundedness of the derivative (Lemma III.4).…”
Section: Introductionmentioning
confidence: 99%